Development and Validation of Reversed Phase HPLC Method for the Estimation of Nevirapine in Pure Form and in Pharmaceutical Dosage Forms - Gowri Sankar, D.; Kumar, D.V.S.P. (Asian Journal of Chemistry, 2016)
A simple, precise reverse phase high performance liquid chromatography (RP-HPLC) method was developed for the estimation of nevirapine in bulk as well as in pharmaceutical dosage forms. The quantification was carried out using a BDS Hypersil C-18 column 250 mm × 4.6 mm i.d., 5 μm particle size in isocratic mode, with mobile phase comprising phosphate buffer and acetonitrile in the ratio of 75 : 25 (v/v). The flow rate was 1.5 mL/min and the detection was carried out at 220 nm. The retention time was 6.748 min. The method produced linear response in the concentration range of 60–130 μg/mL and the percentage recovery ranged from 98.15–99.01.